2003
DOI: 10.1086/368263
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Reduction in Splicing Efficiency of IKBKAP Due to the Major Mutation Associated with Familial Dysautonomia

Abstract: We recently identified a mutation in the I-kappa B kinase associated protein (IKBKAP) gene as the major cause of familial dysautonomia (FD), a recessive sensory and autonomic neuropathy. This alteration, located at base pair 6 of the intron 20 donor splice site, is present on >99.5% of FD chromosomes and results in tissue-specific skipping of exon 20. A second FD mutation, a missense change in exon 19 (R696P), was seen in only four patients heterozygous for the major mutation. Here, we have further characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 40 publications
4
125
0
Order By: Relevance
“…99 Although the mutation occurs in the germline, nociceptive sensory and sympathetic neurons are preferentially affected because Elp1 mis-splicing occurs in these neurons to a greater extent than other cells. 100 Little is known about how Elp1 functions in disease-relevant sympathetic and sensory neurons because most studies have focused on nonneuronal cells from FD patients (eg, fibroblasts and leukocytes) or they have involved Elp1 protein modulation in cells not normally involved in disease. 101e106 Elp1 is a constituent of the heterohexameric transcriptional elongator complex 107 ; therefore, it may be involved in transcriptional regulation.…”
Section: Fd: a Model Of Abnormal Retrograde Ngf Signaling Resulting Imentioning
confidence: 99%
“…99 Although the mutation occurs in the germline, nociceptive sensory and sympathetic neurons are preferentially affected because Elp1 mis-splicing occurs in these neurons to a greater extent than other cells. 100 Little is known about how Elp1 functions in disease-relevant sympathetic and sensory neurons because most studies have focused on nonneuronal cells from FD patients (eg, fibroblasts and leukocytes) or they have involved Elp1 protein modulation in cells not normally involved in disease. 101e106 Elp1 is a constituent of the heterohexameric transcriptional elongator complex 107 ; therefore, it may be involved in transcriptional regulation.…”
Section: Fd: a Model Of Abnormal Retrograde Ngf Signaling Resulting Imentioning
confidence: 99%
“…The embryonic lethality of the Ikbkap Ϫ/Ϫ mice stands in sharp contrast to the clinically observed survival of FD patients beyond the adolescent years. However, this result was anticipated, since the expression of IKAP is completely abolished in the mouse model while variable levels of normal IKAP are produced in FD patients, with marked reduction in the central and peripheral nervous system (13,41). We postulate that there is a tissue-specific minimum IKAP level that is required for normal development.…”
Section: Fig 4 Appearance Of Ikbkapmentioning
confidence: 93%
“…Interestingly, the relative amounts of wild-type and mutant IKBKAP transcripts vary between tissues. In particular, the central and peripheral nervous systems contain the lowest levels of wild-type IKBKAP mRNA and protein (13,41), corresponding to the observed developmental absence and ongoing degeneration of unmyelinated sensory and autonomic neurons seen in FD (2,38). Heterozygous carriers also show reduced IKAP expression; however, no phenotype is evident, suggesting that there is a tissue-specific minimum threshold of IKAP expression required for normal development and maintenance of the nervous system.…”
mentioning
confidence: 99%
“…Exon 20 skipping introduces a nonsense mutation that gives rise to a truncated Elp1 protein (Elp1 Tr ) that is rapidly degraded (Slaugenhaupt et al, 2001). For poorly understood reasons that may relate to differences in splicing fidelity, the ratio of normal-tomutant ELP1 mRNA varies across cell types and is particularly low in peripheral sensory and sympathetic neurons in individuals with FD (Cuajungco et al, 2003;Slaugenhaupt et al, 2001). The relatively low levels of Elp1 protein in sympathetic and sensory neurons correlate with early postmortem studies of individuals with FD who showed dramatic reduction in the number of sensory, sympathetic and some parasympathetic neurons (Axelrod et al, 1981;.…”
Section: Introductionmentioning
confidence: 99%